Investigation of Two-Stage Fuel Burning in Oil-and-Gas-Fired Boilers - G. I. Zhikhar; I. G. Zhikhar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives results of the investigation of two-stage fuel burning in oil-and-gas-fired boil-